Analyzing students' performance in calculus using fuzzy anp: an innovative approach / Amirah Hani Abdul Hadi ... [et al.] - Abdul Hadi, Amirah Hani; Abdullah, Nur Solihah Khadhiah; Rani, Norhamimah; Jaafar, Ruhana; Mohd Akhir, Noor Erni Fazlina (2020)
Universiti Teknologi MARA offers many diploma programs with different study plans for students to enroll. One of the diploma programs offered is Diploma in Computer Science (CS110) which requires students to take Calculus in their study plan. However, previous students' achievements have shown that many Computer Science students performed badly in this subject. There must be underlying reasons or factors that lead to this low achievement. The identification of the factors involved is crucial in measuring and analyzing the students' performance. For that reason, Fuzzy Analytic Network Process (FANP), a decision-making instrument was constructed in this project, focusing on the selection process to calculate, rank and identify the most influential factor that contributes to the students' performance in Calculus. Three factors and eleven sub-factors were analysed. Then, the percentage value of each sub-factor was calculated using FANP, which has subsequently produced the ranking for each sub-factor. By identifying the factor, both students and lecturers can work together to find ways to overcome the problem. The findings show that sub-factor of relationship between students and lecturer (S23) hits the first place in the ranking order followed by parenting style (S13) and instructional strategies and methods (S22).